ANALISIS PROBLEMATIKA PEMBELAJARAN PADA SISWA KELAS V DI SDN 101775 SAMPALI - Dwi Tarisya; Isyrofirrahmah Isyrofirrahmah; Khairunnisa Nasution; Monalisa Chaira Nainggolan; Rehan Shafira; Rahmilawati Ritonga (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
This study aims to analyze the learning problems faced by fifth-grade students at SDN 101775 Sampali, particularly regarding the role of parents in supporting their children's learning process. A descriptive qualitative approach was employed, using observation and interviews with the homeroom teacher as the main data source. The results indicate that the low level of parental involvement negatively affects students’ learning attitudes and academic achievement, such as poor academic performance, tardiness, absenteeism, and weak basic reading skills. Economic factors and parental fatigue are the main reasons for the lack of guidance at home. This study emphasizes that parental involvement plays a crucial role in supporting children's motivation, resilience, and academic success. Collaboration between schools and parents is an essential strategy to create a more conducive and supportive learning environment for students’ overall development.